An Evaluation of student support services in open and distance learning at the University of Namibia - Mowes, Delvaline Lucia (Stellenbosch : University of Stellenbosch, 2008)
Distance education and open and flexible learning policies have done much to extend accessibility to higher education throughout the world. However, distance education is not just a move away from learning in the classroom. It is a complete paradigm shift and when delivering learning materials outside the classroom across any distance, it is important that technologies and techniques support students. Against this background, the case has been made that the provision of student support services, according to the diverse needs and expectations of adult distance education students, should be an integral part of the provision of open and distance learning. The focal point of this study was to evaluate student support services, provided at the northern campus of the University of Namibia, from a student perspective. A combination of both quantitative and qualitative methodologies was chosen and data were collected by means of a literature review and a questionnaire, supplemented with open-ended questions. The subjects of the study were second- and third-year B.Ed. students from the northern campus of the University of Namibia. The results of this study have provided evidence that adult distance education students indeed value the provision of student support services. Specifically, students in this study placed the greatest importance on student support services related to getting started with their studies, for example orientation sessions about available student support services and contact and communication with tutors and fellow students by means of vacation schools, face-to-face tutorials on Saturdays at regional centres and support through study groups. One of the conclusions of the study was that the institutional policy and the role of management are crucial in the establishment of an effective student support model to facilitate distance learning. The following recommendations were formulated: The University’s Centre for External Studies (CES) should conduct periodic and regular evaluation studies of its distance education students to design, develop and provide student support services that will be tailored to students’ specific needs and expectations. CES should pay attention to support services that help reduce barriers if it is to attain its mission of making quality higher education more accessible. CES should provide adequate training to tutors to prepare them for the special challenges presented by open and distance learning. CES should design and implement an appropriate Information and Communication Technology (ICT) course to empower distance education students adequately for the use of modern ICT.